Premio al mejor revisor de Ecosistemas del bienio 2015-2016 - Rodríguez-Echeverría, Susana; Alonso, Álvaro; Amoroso, Mariano; Blanco, Juan Antonio; Lacerot, Gissell; Molina-Morales, Mercedes; Puerta-Piñero, Carolina; Vargas, Renzo; Jiménez-Eguizábal, Leyre (Ecosistemas, 2017)
Rodríguez-Echeverría, S., Alonso, Á., Amoroso, M., Blanco, J.A., Lacerot, G., Molina-Morales, M., Puerta-Piñero, C., Vargas-Rodríguez, R., Jiménez-Eguizábal, L. 2017. Premio al mejor revisor de Ecosistemas del bienio 2015-2016. Ecosistemas 26(1): 89. Doi.: 10.7818/ECOS.2017.26-1.13